Arthroplasties for hip fracture in adults - Sreekanta, A; Parker, MJ; Wood, H; Glanville, JM; Cook, J; Griffin, XL (Cochrane Collaboration, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the relative effects (benefits and harms) of different designs, articulations, and fixation techniques of arthroplasties for treating hip fractures in adults. This will include assessment of the relative effects (benefits and harms) of the following. THR versus HA Cemented versus uncemented arthroplasties Alternative articulation designs in THA Different designs of HA, e.g. bipolar versus unipolar.